2016
DOI: 10.1111/ijac.12531
|View full text |Cite
|
Sign up to set email alerts
|

Ti3SiC2 Reinforced ZA27 Alloy Composites with Enhanced Mechanical Properties

Abstract: This work reports the fabrication and mechanical properties of Ti3SiC2 reinforced Zn‐27 wt. % Al alloy (denoted as ZA27). A total of 10–40 vol. % Ti3SiC2 reinforced ZA27 alloy composites were synthesized by hot pressing mechanically alloyed mixtures of Ti3SiC2 and ZA27 powders. Among the fabricated composites, 20 vol. % Ti3SiC2/ZA27 composite possesses the highest room temperature tensile strength, bending strength and Vickers hardness of 339 MPa, 593 MPa, and 1.13 GPa, respectively. The improved mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…No extra phases were found, which indicated that no reaction occurred between Ti 3 SiC 2 and ZA27 matrix. The similar conclusion can also be found in our prior work 17 . Differently, some new phases appeared in Ti 3 AlC 2 /ZA27 and Ti 2 SnC/ZA27 composites.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…No extra phases were found, which indicated that no reaction occurred between Ti 3 SiC 2 and ZA27 matrix. The similar conclusion can also be found in our prior work 17 . Differently, some new phases appeared in Ti 3 AlC 2 /ZA27 and Ti 2 SnC/ZA27 composites.…”
Section: Resultssupporting
confidence: 91%
“…The similar conclusion can also be found in our prior work. 17 Differently, some new phases appeared in Ti 3 AlC 2 /ZA27 and Ti 2 SnC/ZA27 composites. As plotted in Figure 1B, the major phases are Al, Zn, and Ti 3 AlC 2 , while some small peaks signed as Al 0.64 Ti 0.36 and TiC are also detected.…”
Section: Xrd Analysis Of the Compositesmentioning
confidence: 92%
“…파괴가 용이하게 일어나기 때문에 용도가 제한될 수 밖에 없 다 [1][2][3][4][5]. 따라서 아연 합금의 결정립 미세화 [6][7][8][9][10], 석출 [11] 및 분산강화 [12] 그리고 강소성 가공 [13,14]…”
unclassified